Whose knowledges? - Shdaimah, Corey S. (Criminological encounters, 2018)
Recent scholarship across disciplines reflects renewed interest in making social science relevant to social and policy change (Burawoy, 2005; Flyvbjerg, 2001). At the same time, professional organizations have struggled to articulate ethical obligations towards research participants. In this article we draw on our own research with street-based sex workers to explore the implications for scholarship and policy when researchers allow their studies to be guided by the voices of study participants rather than their own assumptions and hypotheses (Capous-Desyllas & Forro, 2014). We describe how our interpretation evolved upon adopting a feminist, qualitative stance that recognizes the agency and authority of respondents to guide the analysis. We join a growing group of scholars who draw attention to the multidimensionality of sex workers' identities, goals, and daily lives to provide a fuller picture of their lives and experiences (Cheng, 2013; Hail-Jares, Shdaimah, & Leon, 2017). Such a picture inevitably shifts from the options of repair, rescue, or repression as women talk back. Intentional engagement also works against the tendency to "other" the objects of our research and illuminates the systemic factors that shape women's choices and lives. Our insights apply to research with vulnerable or stigmatized populations across criminological and socio-legal contexts and to criminal justice policy.